Survival Strategies of Madurese Ethnic Street Vendors in Surabaya City During the Covid-19 Pandemic - Dayanti, Fitria; Harianto, Sugeng (TEMALI : Jurnal Pembangunan Sosial, 2023)
Since the emergence of Covid-19, the lives of informal workers have changed, and street vendors are no exception. This happened because government policies limited the space for people to move, impacting informal workers' income. There is a demand to survive amid declining income during the Covid-19 pandemic, requiring strategies so that informal workers can survive. This article explores the problems experienced by overseas street vendors during the Covid-19 Pandemic. It analyzes the survival strategies by conducting a case study of ethnic Madurese street vendors in Surabaya, Indonesia. This study uses a descriptive qualitative method with a knife of theoretical analysis survival mechanism of James C Scott. This research was conducted in 2021 in the city of Surabaya. Data collection was carried out utilizing observation and in-depth interviews. The results show that several survival strategies are used by overseas street vendors, especially ethnic Madurese as urban people, namely reducing employee salaries, spending management and making priority scales, doing side jobs, and relying on social relations.